Cytoprotective and immunostimulatory properties of Stachys sieboldii and Stevia rebaudiana under metabolic stress in rats - Pozdnyakova, Ye.V.; Murzatayeva, A.M.; Sailau, A.S. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2026)
This study evaluated the protective effects of Stachys sieboldii and Stevia rebaudiana extracts on bone marrow and spleen cells in rats subjected to a high-fat, high-sucrose (HFHS) diet. Prepubertal Wistar rats were randomly assigned to four groups (control, HFHS, HFHS+Stachys, HFHS+Stevia) and maintained for 30 days. Spleen and bone-marrow cellularity and cell viability were quantified. The HFHS diet increased the proportion of non-viable cells and reduced nucleated-cell counts in both organs. Stachys primarily enhanced splenic immune-cell proliferation (higher nucleated-cell concentration), whereas Stevia produced a stronger cytoprotective response, reducing the fraction of dead cells in bone marrow. Taken together, these findings suggest complementary actions: Stachys acts as a pro-proliferative modulator of splenic immune cells, while Stevia protects hematopoietic cells from HFHS-induced damage. These results highlight the potential of these plant extracts as dietary components for supporting immune and hematopoietic function and provide a basis for their further investigation in preventive and immunomodulatory applications.
Егеуқұйрықтардағы күйзеліс метаболизмі кезіндегі Stachys sieboldii және Stevia rebaudiana өсімдіктерінің цитопротекторлық және иммунитет стимулдеуші қасиеттері
Цитопротекторные и иммуностимулирующие свойства Stachys sieboldii и Stevia rebaudiana в условиях метаболического стресса у крыс
Keywords: immunity; bone marrow; spleen; high-fat diet; HFHS; Stevia rebaudiana; Stachys sieboldii